Positional differences in the cardiorespiratory, autonomic, and somatic profiles of professional soccer players - Semjon, M.; Botek, M.; Svozil, Z.; McKune, A. J. (Acta Gymnica, 2016)
Methods: All players (N = 120) were divided into six groups according to field positions: goalkeeper (GK; n = 11), external defenders (ED; n = 15), central defenders (CD; n = 18), external midfielders (EM; n = 18), central midfielders (CM; n = 24) and forwards (F; n = 34). Players underwent anthropometrical and heart rate variability (HRV) assessment, and a maximal incremental running test in order to obtain maximal oxygen uptake (VO2max) and heart rate. HRV variables were transformed using the natural logarithm (Ln).